Diagnosis of the flowers and ornamental plants sector of the municipality of Macapá (Research, Society and Development, 2022)
The Brazilian market for flowers and ornamental plants mobilizes values in excess of R$ 5 billion. This research aimed to characterize the flower and ornamental plant sector in the City of Macapá, to analyze the scenario existing in Amapá. The participants of the research were producers and/or merchants of flowers and ornamental plants, whether individuals or legal entities existing in the City of Macapá, State of Amapá. For the socio-economic survey, interviews were conducted with those who produce and/or sell flowers and ornamental plants. The survey was conducted through questionnaires scripted interviews. The data were organized in order to perform a register of flower and ornamental plant producers in the City of Macapá, and the information gathered during the interviews related to the socio-economic questionnaire served to conduct an in-depth study of these characteristics of those who make up the sector. With this work was carried out a reliable characterization of the sector of flowers and ornamental plants in Macapá, as well as with the preparation of the Catalogue of Flowers and Ornamental Plants. A total of 166 plant species commercialized in Macapá were found through 38 interviews. The interviews conducted with the entrepreneurs of the Flowers and Ornamental Plants sector in the city allow us to conclude that the sector is essentially a retailer and composed, predominantly, of companies without formalization. Most traders and producers do not have a high degree of professionalization, although they have a great knowledge about plants and business administration.